DOES DECISION PROCESS MATTER? A STUDY OF STRATEGIC DECISION-MAKING EFFECTIVENESS. - Dean, J. W.; Sharfman, M. P. (Academy of Management Journal, 1996)
This study examined whether strategic decision-making processes are related to decision effectiveness, using a longitudinal field study design. We studied 52 decisions in 24 companies to determine ...